One Core Phase Shifting Transformer for Control of the Power Flow Distribution in Electric Networks - Golub I.V. (Problems of the Regional Energetics)
This paper presents the variant of phase shifting transformer that is made, unlike from traditional technology, on the basis of only one magnetic core. The paper describes the methodology related to the analysis of operation modes of device and its components. Additionally it presents a mathematical model of device with determines the relationship between input and output electric quantities as well as own longitudinal and transverse parameters of an equivalent circuit of phase shifting transformer (PST). Proposed configuration of PST is interesting from an economic and operational consideration; enable continuous control of power flow distribution in electric networks as a result of regulation a phase shift angle between input and output voltages of device.